Penguins and Antarctica : a nonfiction companion to Eve of the emperor penguins - Osborne, Mary Pope.; Boyce, Natalie Pope.; Murdocca, Sal; Osborne, Mary Pope. (New York : Random House, 2008)
Jack and Annie share what they learned through their research on the penguins of Antarctica and the harsh conditions in which they live at the South Pole.
"A Stepping stone book."
Includes bibliographical references, filmography, and index.
4.8
3-6
Keywords: Emperor penguin -- Antarctica -- Juvenile literature; Emperor penguin -- Antarctica; Penguins; Emperor penguins; Penguins; Antarctica -- Juvenile literature; Antarctica; Antarctica